Implementasi Kegiatan Belajar Berbasis Proyek Melalui Metode Bercerita dalam Mewujudkan Pembelajaran Aktif Anak Usia Dini di TK Islam Al Azhar 29 BSB Semarang - Azzahra, Hilyatul Karimah; Muslam, Muslam (PAKAR Pendidikan, 2025)
This study examines the implementation of project-based learning (PBL) through storytelling as a strategy to foster active learning in early childhood education at Al Azhar 29 BSB Semarang Islamic Kindergarten. The research highlights the pivotal role of teachers as facilitators in encouraging creativity and engagement, enabling children to explore their interests through project-based activities. Storytelling is emphasized as an effective method to enhance language skills, empathy, social sensitivity, and moral values in young learners. The findings reveal that integrating PBL with storytelling significantly improves children's focus, cognitive abilities, and overall learning experience. This approach creates a stimulating environment that nurtures critical thinking, collaboration, and creativity. Furthermore, the study underscores the importance of thematic and well-planned activities to maintain children's interest and participation. The implementation of this method aligns with national educational objectives, equipping children to face future academic and developmental challenges effectively.